In-depth analysis of the replication cycle of Orpheovirus - Fernanda Souza (Virology Journal, 2019)
Abstract Background After the isolation of Acanthamoeba polyphaga mimivirus (APMV), the study and search for new giant viruses has been intensified. Most giant viruses are associated with free-living amoebae of the genus Acanthamoeba; however other giant viruses have been isolated in Vermamoeba vermiformis, such as Faustovirus, Kaumoebavirus and Orpheovirus. These studies have considerably expanded our knowledge about the diversity, structure, genomics, and evolution of giant viruses. Until now, there has been only one Orpheovirus isolate, and many aspects of its life cycle remain to be elucidated. Methods In this study, we performed an in-depth characterization of the replication cycle and particles of Orpheovirus by transmission and scanning electron microscopy, optical microscopy and IF assays. Results We observed, through optical and IF microscopy, morphological changes in V. vermiformis cells during Orpheovirus infection, as well as increased motility at 12 h post infection (h.p.i.). The viral factory formation and viral particle morphogenesis were analysed by transmission electron microscopy, revealing mitochondria and membrane recruitment into and around the electron-lucent viral factories. Membrane traffic inhibitor (Brefeldin A) negatively impacted particle morphogenesis. The first structure observed during particle morphogenesis was crescent-shaped bodies, which extend and are filled by the internal content until the formation of multi-layered mature particles. We also observed the formation of defective particles with different shapes and sizes. Virological assays revealed that viruses are released from the host by exocytosis at 12 h.p.i., which is associated with an increase of particle counts in the supernatant. Conclusions The results presented here contribute to a better understanding of the biology, structures and important steps in the replication cycle of Orpheovirus.